Pemanfaatan Media Digital dalam Sosialisasi Pencegahan Pernikahan Dini: Pengabdian - Darmawan, Femas Agusta Regi; Yustiono, Yustiono; Niswah, Asna Mufidatun; Hafizah, Inesia Fais; Lutfiyah, Vera; Paraswati, Yunia Putri; Shodikin, Moh.; Toyib, Madini Alfi; Andrean, Muhammad; Saputri, Febby Bella; Mega Hardijanti Suryani; Fitrianingtyas, Rizki (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Stunting and early marriage are crucial issues that impact the quality of human resources in Indonesia, including in Klungkung Village. Prevention requires an innovative and adaptive approach, especially for the younger generation who are familiar with digital technology. This community service activity aims to increase awareness and understanding of the dangers of stunting and early marriage among adolescents and parents in Klungkung Village through digital media in the form of educational videos and interactive QR code banners. The methods used included developing research-based materials, producing videos, installing banners in strategic locations, and evaluating community response. The results showed that interactive digital media effectively attracted attention, facilitated access to information, and increased public understanding, thus becoming an effective and sustainable means of delivering health and social messages in rural areas.